2020
DOI: 10.3947/ic.2020.52.3.360
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Cross-Reactivity of Rapid Diagnostic Tests for Norovirus and Rotavirus in a Real Clinical Setting

Abstract: Background: Rapid diagnostic test (RDT) of norovirus and rotavirus is commonly used for outbreak screening and patient management. Varying accuracy of the test and cross-reactivity has been reported and could affect the outcome of management. The primary purpose of this study is to provide the accuracy of norovirus and rotavirus rapid diagnostic tests and to analyze the cross-reactivity of both tests. Materials and Methods: Stool samples collected from every acute diarrhea patient aged <15 years old who was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, PCR allowed the rapid testing of higher samples and provided important evidences for conducting additional tests with pathogen culture and to implement monitoring systems in the future. Recent studies comparing PCRs and cultures have shown high specificity [ 40 ], suggesting that the diagnostic reliability of PCR will also increase in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, PCR allowed the rapid testing of higher samples and provided important evidences for conducting additional tests with pathogen culture and to implement monitoring systems in the future. Recent studies comparing PCRs and cultures have shown high specificity [ 40 ], suggesting that the diagnostic reliability of PCR will also increase in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, their performance remains controversial, and the obtained results may remain doubtful in asymptomatic subjects due to low viral loads. Furthermore, only few studies have investigated their validity in tropical countries, such as those conducted by Ope et al [13] and Thangjui et al [14]. The present study (i) determined the correlation between RDT results and RVA viral load, as assessed by cycle threshold (Ct) values; (ii) assessed the diagnostic accuracy of the Bioline Rota/ Adeno SD RDT and (iii) determined the effect of sampling period on RDT results.…”
Section: Introductionmentioning
confidence: 90%
“…Another study reported that VIKIA1 Rota-Adeno rapid test kit had high specificity (91.6%) but low sensitivity (44.8%) of rotavirus detection in clinical settings [32]. A study conducted in refugee camps on the border between Kenya and Somalia reported comparable findings of sensitivity (83.1%) and specificity (99.3%) for ImmunoCard STAT!1 Rapid Diagnostic Test kit [33].…”
Section: Plos Onementioning
confidence: 98%